1986
DOI: 10.1177/009365086013004004
|View full text |Cite
|
Sign up to set email alerts
|

How Media Use and Reliance Affect Knowledge Level

Abstract: Results of studies of the relation between media consumption and political knowledge are mixed. This study looked at three media consumption variables—reliance, media use, and focused media use—and their relation to knowledge of issues in a state tax referendum. Focused media use was defined as reading or viewing of news about state and local politics. Reliance on TV news correlated negatively with knowledge of issues. Reliance on newspapers did not correlate at all. Focused TV news use correlated more highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(17 citation statements)
references
References 29 publications
0
15
0
2
Order By: Relevance
“…This may reflect that devoted use of a given news form in the absence of other news forms produces more learning from that form than when learning is distributed across various forms—the essence of our argument for diminishing returns as described below. However, variations in measurement and analysis across these studies make this interpretation very tentative; moreover, the findings are inconsistent (e.g., Culberston & Stempel, 1986; McLeod & McDonald, 1985). Beyond studies of dependency and reliance, McDonald, Sietman, and Li (2004) found that the diversity of media used had a significant impact on news knowledge above and beyond use of specific forms of media.…”
Section: Theoretical Bases Of Intramedia Interactionmentioning
confidence: 97%
See 1 more Smart Citation
“…This may reflect that devoted use of a given news form in the absence of other news forms produces more learning from that form than when learning is distributed across various forms—the essence of our argument for diminishing returns as described below. However, variations in measurement and analysis across these studies make this interpretation very tentative; moreover, the findings are inconsistent (e.g., Culberston & Stempel, 1986; McLeod & McDonald, 1985). Beyond studies of dependency and reliance, McDonald, Sietman, and Li (2004) found that the diversity of media used had a significant impact on news knowledge above and beyond use of specific forms of media.…”
Section: Theoretical Bases Of Intramedia Interactionmentioning
confidence: 97%
“…For instance, research on media reliance has examined how reliance on a given medium influences learning from a different medium. That is, some research has shown that those who are reliant on a given news media form learn more from that form than those who are reliant on a different form (e.g., Culbertson & Stempel, 1986). This may reflect that devoted use of a given news form in the absence of other news forms produces more learning from that form than when learning is distributed across various forms—the essence of our argument for diminishing returns as described below.…”
Section: Theoretical Bases Of Intramedia Interactionmentioning
confidence: 99%
“…Most methodological examinations of this topic argue that simple exposure measures are inadequate to tap the relative influence of communication sources (e.g., Chaffee & Schleuder, 1986;Culbertson & Stempel, 1986;McLeod & McDonald, 1985), suggesting instead the use of some alternative form of self-report measure. This investigation employed the self-report measure of information utility of sources in order to ensure equivalency across media sources.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of such studies compared print and television, and found that print was superior compared to other media when it came to information processing measures (Brown, 1978;Furnham & Gunter, 1987;Wilson, 1974). Other studies also found that print was a better predictor of detailed political and current affairs knowledge (Chaffee & Frank, 1996;Culbertson & Stempel, 1986). Meanwhile, these claims of ‛print superiority' were challenged by other scholars who reported no modality differences (Stauffer, Frost, & Rybolt, 1981) or that television was a more effective medium for information processing compared to print (Heim, Asting, & Schliemann 2002;Just & Crigler, 1989;Kozma, 1994).…”
Section: Experimental Researchmentioning
confidence: 99%